The Place of FDG PET/CT in Renal Cell Carcinoma: Value and Limitations - Liu, Yiyan (Frontiers in Oncology, 2016)
Unlike for most other malignancies, application of FDG PET/CT is limited for renal cell carcinoma (RCC), mainly due to physiological excretion of FDG from the kidneys, which decreases contrast between renal lesions and normal tissue, and may obscure or mask the lesions of the kidneys. Published clinical observations were discordant regarding the role of FDG PET/CT in diagnosing and staging RCC, and FDG PET/CT is not recommended for this purpose based on current national and international guidelines. However, quantitative FDG PET/CT imaging may facilitate the prediction of the degree of tumor differentiation and allow for prognosis of the disease. FDG PET/CT has potency as an imaging biomarker to provide useful information about patient’s survival. FDG PET/CT can be effectively used for postoperative surveillance and restaging with high sensitivity, specificity and accuracy, as early diagnosis of recurrent/metastatic disease can drastically affect therapeutic decision and alter outcome of patients. FDG uptake is helpful for differentiating benign or bland emboli from tumor thrombosis in RCC patients. FDG PET/CT also has both higher sensitivity and accuracy when compared to bone scan to detect RCC metastasis to the bone. FDG PET/CT can play a strong clinical role in the management of recurrent and metastatic RCC. In monitoring the efficacy of new target therapy such as tyrosine kinase inhibitors (TKI) treatment for advanced RCC, FDG PET/CT has been increasingly used to assess the therapeutic efficacy, and change in FDG uptake is a strong indicator of biological response to TKI.